Environmental impact assessment and potentials of material efficiency using by-products and waste materials. (16th May 2023) - Aslani, Alireza; Hachem-Vermette, Caroline; Zahedi, Rahim
Graphical abstract: Highlights: Assessing the reduction potential of GHG emissions associated with decreasing the amount of PC used in concrete. Introducing various by-products and waste materials of high-energy intensive processes. Assessing environmental impacts of the by-products/wastes materials that can substitute the portland cements to be utilized in concrete and building envelope walls. Assessing potential of the implementation of these by-products and wastes in Canada. Abstract: As sustainability is becoming a priority in the construction industry, concerns associated with the environmental impacts of the production and use of Portland cement (PC) are being raised. To respond to this challenge and among different strategies of material efficiency, the potential of by-products and recycling wastes to produce eco-friendly cement-based or cement-less construction materials is given greater emphasis. This research investigates the environmental assessment and carbon footprint of different building envelope walls using by-product and waste materials of energy-intensive processes including power plants, and steel and glass industries. Four different products that can be used in the concrete as the replacement of Portland cement including fly ash, ground granulated blast-furnace slag (GGBS), Glass powder, and mix design of these materials are compared with the regular concrete mix to be used as an envelope wall. After that, the potentials of production and consumption of these materials in the concrete are assessed in Canada. Results show that GGBS concrete with 287 kg CO2 eq per m3 has the lowest CO2 emissions compared with other by-products/waste-used concrete. The CO2 emissions of fly ash concrete are 37% higher than GGBS and glass powder concrete has 50% higher CO2 emissions compared with GGBS concrete. Also, among different environmental damages that concrete would be responsible for, damage to human health has the highest impact on the environment. Fly ash and glass powder concrete have also the highest environmental damage to human health even than regular mix. GGBS concrete has the lowest environmental impact compared with other products that can be considered as a great replacement for PC. Due to the concrete demand exist in Canada, all studied by-products and waste can be fully used in the concrete industry.